PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PEMAHAMAN SANTRI PADA PEMBELAJARAN FIKIH TENTANG PENYELENGGARAAN JENAZAH DI PONDOK PESANTREN AL FALAH PUTERA BANJARBARU - Baidhawi Baidhawi (ADDABANA: Jurnal Pendidikan Agama Islam, 2018)
This study discusses the application of demonstration methods to improve students' understanding of Jurisprudence learning about the organization of the body at the Al Falah Putera Banjarbaru Islamic Boarding School which includes how to apply the method, understanding students with the implementation of the demonstration method and the reason for choosing the demonstration method. This study aims to find out how the application of demonstration methods to improve students understanding of Jurisprudence learning about the organization of the body at the Al Falah Islamic Boarding School in Putera Banjarbaru and what are the factors that influence the application of the demonstration method to improve students' understanding of Jurisprudence learning about the implementation of bodies in Islamic boarding schools Al Falah Putera Banjarbaru. Subjects in this study were the third-grade students of Wustha at the Al Falah Putera Islamic Boarding School, while in the object of this study were the method of demonstration on the teaching of Jurisprudence related to the organization of the body. In extracting data, researchers used observation, interview, and documentation techniques. Data processing techniques are carried out by editing, data classification, and data interpretation. Furthermore, it was analyzed with qualitative descriptive analysis and deducted vertically. Based on the results of the study that the application of the demonstration method to improve students' understanding of Jurisprudence learning about the organization of the body at the Al Falah Islamic Boarding School in Putera Banjarbaru, in general, has been carried out quite well, this is influenced by several factors, including religious factors, santri factors, time allocation factors , facilities and infrastructure factors, as well as supporting environmental factors so that the learning of the body is implemented. Keywords: Improved Understanding, Learning Fiqh, Santri, Islamic Boarding Schools.